ChemInform Abstract: One‐Pot Parallel Synthesis Approach to Secondary Amines Based on the Reductive Amination of Ketones. Issue 52 (29th December 2014) - Bogolubsky, Andrey V.; Moroz, Yurii S.; Pipko, Sergey E.; Panov, Dmitriy M.; Konovets, Anzhelika I.; Doroschuk, Roman; Tolmachev, Andrey
Abstract A set of arbitrarily chosen acyclic and cyclic, alkyl and aryl ketones as well as amines (twenty each) are converted in this one‐pot approach to build up a library of secondary amines.